Reminiscences : A Journey through Particle Physics - Melissions, Adrian (Singapore: World Scientific, 2013)
A personal recount in areas of particle physics and related fields as a research physicist for over 50 years, Adrian Melissinos' insights into the ways that general research was carried out, as well as the evolution of particle physics from 1958 to 2008 will prove valuable to science history enthusiasts, as well as particle physicists.Be it conventional accelerator experiments, the use of microwave techniques in search of cosmic axions, or taking advantage of high power lasers to observe light-by-light scattering, the excitement of searching for something new in the face of failures and then successes is enriching, and the collaboration with gifted and outstanding colleagues and students proves insightful.A hybrid of personal reminiscences and a professional journey, readers get to relive the joy and excitement of researching and teaching in small groups during those early years while gaining a partial historical perspective of particle physics since 1958 -- all in Reminiscences: A Journey through Particle Physics. /remove
Name index 191-194p.; Subject index 195-202p.
Keywords: Deep inelastic scattering; Photoinjectors; Axions